2018
DOI: 10.1088/1361-6595/aaeccd
|View full text |Cite
|
Sign up to set email alerts
|

The effects of secondary electron emission on plasma sheath characteristics and electron transport in an ${\bf{E}}\times {\bf{B}}$ discharge via kinetic simulations

Abstract: Hall-effect thrusters, which are electrostatic devices based on an E B plasma discharge, have successfully been used as satellite propulsion systems for the last few decades. However, the presence of anomalous electron cross-field transport is still poorly understood, and involves complex and strongly coupled mechanisms such as azimuthal electron drift instabilities and intense secondary electron emission (SEE) from the thruster walls. The present work focuses on the relative importance of these two phenomena.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 44 publications
(128 reference statements)
2
30
1
Order By: Relevance
“…The code is parallelized via MPI through a domain decomposition. It has been verified with the 1D helium benchmark of Turner et al [19] (further details in [28,29]) and extensively used to simulate the radial-azimuthal plane of a Hall Thruster [28,30,31]. For this benchmark, the code was adapted to the axial-azimuthal plane and accelerated via a load-balancing algorithm (adjusting periodically the size of each processor domain to have approximately the same number of particles inside each processor).…”
Section: Group Lpp: T Charoy a Tavant A Bourdon P Chabertmentioning
confidence: 99%
“…The code is parallelized via MPI through a domain decomposition. It has been verified with the 1D helium benchmark of Turner et al [19] (further details in [28,29]) and extensively used to simulate the radial-azimuthal plane of a Hall Thruster [28,30,31]. For this benchmark, the code was adapted to the axial-azimuthal plane and accelerated via a load-balancing algorithm (adjusting periodically the size of each processor domain to have approximately the same number of particles inside each processor).…”
Section: Group Lpp: T Charoy a Tavant A Bourdon P Chabertmentioning
confidence: 99%
“…As a mean to assess the quality of our results, we have performed three Particle-In-Cell Monte Carlo-Collisions (PIC-MCC) simulations, with the code LPPic that was already verified via the 1D Helium benchmark of Turner et al 38 and extensively used to simulate the radial-azimuthal plane of a Hall Thruster. 17,39 The code was adapted to simulate the axial-azimuthal plane and we present here three cases with a simulation model similar to the one used in the 2D benchmark of Charoy et al 40 In this case, an axial electric field is created by a potential difference imposed between an anode at 200 V and a cathode at 0 V (see Fig. 15).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Finally, a regime of relaxation sheath oscillations observed in 1D-radial model (Sydorenko et al 2009) has been also observed in the 2D(r,q) model of Tavant et al (2018). In particular, three regimes have been identified when varying the effective SEE coefficient.…”
Section: ____________________________________________________________mentioning
confidence: 55%
“…Secondly, short wavelength instabilities with a significantly large component along the magnetic field reduce to the unmagnetized (ion-sound) form as seen from the analytical solution of the dispersion relation. Recent models (Héron-Adam 2013, Hara-Cho 2017, Croes et al 2017, Jahnunen et al 2018b, Tavant et al 2018, Taccogna et al 2019 have added the radial coordinate resolving the direction along the magnetic field and accounting for the sheath boundary conditions. They have shown that the full ion sound regime is not realized, but a more effective regime of discrete cyclotron resonance instabilities (again inverse cascade towards low wavenumbers) occur.…”
Section: ____________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation